Isolation and characterization of a rough colony type of Neisseria gonorrhoeae. - Jacobs, N F (1977)
A new colony type of Neisseria gonorrhoeae was detected in the primary cultures from 8 of 180 men with gonococcal urethritis. This colony type contrasts with those previously described by having a rough and irregular surface. In six of the eight cases, the rough form predominated. The distinctive morphology of the rough colony variant could be maintained indefinitely by selective subculture. By electron microscopy, organisms taken from rough colonies of each of the eight isolates were piliated. Antimicrobial susceptibilities of type 1 and rough clones derived from the same patients were identical for ampicillin, penicillin, tetracycline, and spectinomycin. After inoculation of rough colonies into subcutaneous chambers in mice and guinea pigs, type 1 colonies predominated in cultures of material obtained from the chambers. This new piliated colony type of N. gonorrhoeae may provide an opportunity to investigate factors other than pili that contribute to gonococcal virulence.